Volleyball Service Skill Level (Empirical Study on Pulokulon 2 State Middle School Students) - Aunur Rohman, Raihan; Jariono, Gatot; Nurhidayat, Nurhidayat (Universitas PGRI Palembang, 2025)
Abstract This research aims to determine the level of top serve skills in volleyball games of students at SMP Negeri 2 Pulokulon. The sample in this study was taken from one class at level VIII, which consisted of 32 students (17 boys and 15 girls). This type of research is a type of quantitative research with a descriptive approach. The instrument used is a top serve skill test in volleyball, with an assessment using the top serve accuracy test (AAHPER serving accuracy test). The results showed that 3 (9.38) students had the upper level of service skills in the very good category, 2 (6.25%) students had the good category, 20 (62.5%) students had the medium category, 4 (12.5%) have a poor category, and 3 (9.37%) have a bad category. So it can be concluded that the average level of volleyball service skills in class VIII students at SMP Negeri 2 Pulokulon is in the medium category, namely with a percentage of 62.5% for a total of 20 students. Keywords: Skill Level, Top Serve, Volleyball